Bunny dreams - McCarty, Peter (Henry Holt and Company, 2016)
"In bunny dreams, anything can happen. A bunny might know the ABCs, or count by 1-2-3s. A bunny might find the perfect carrot. A bunny might hop, hop, hop. or even fly! But every bunny needs a cozy place to rest"--